High-productive recovery and purification of superoxide dismutase from Tetraselmis chuii using integrated ultrasonication–aqueous two-phase system - Kwa, Jia Sim; Tan, Siu Chee; Ariff, Arbakariya B.; Khayat, Mohd Ezuan; Mohamed, Mohd Shamzi; Faizal Wong, Fadzlie Wong (Taylor and Francis, 2025)
Superoxide dismutase (SOD) is the first line of antioxidant defense against reactive oxygen species, and it has found wide application in cosmetic and supplementary products. Thus, supplementation of exogenous SOD can restore the antioxidant defense system. Tetraselmis chuii is rich source of SOD, has low toxicity, exhibits high resistance toward culture conditions and grows rapidly, gaining significant attention. However, whole-cell SOD has poor bioavailability due to degradation of the SOD in gastrointestinal tract. Therefore, SOD bioseparation is needed for the nutraceutical/biopharmaceutical application before its administration via parenteral route, to increase its potency. This study aimed to recover and purify SOD from T. chuii using ultrasonication and poly(ethylene glycol) (PEG)–phosphate aqueous two-phase system (ATPS). Furthermore, two schemes, ultrasonication coupled in tandem with ATPS and integrated ultrasonication–ATPS, were compared. SOD activities of 73.3 ± 24.8 U/mL were obtained using distilled water under the ultrasonication conditions of: 4000 µg/mL cell concentration, 30% amplitude, and 2-min duration. Next, under optimal ATPS conditions: 15% (w/w) PEG2000 and 12.5% (w/w) phosphate buffer (pH 7) with 0.04% (w/w) crude load, 87.4 ± 8.0% activity recovery, and 4.9 ± 0.3 purification factor were attained. The integrated ultrasonication–ATPS system gave a higher productivity (138.8 vs. 73.3 U/mL/h) and activity recovery (92.6 ± 0.6 vs. 87.4 ± 8.0%), albeit with lower purification factor (2.3 ± 0.1 vs. 4.9 ± 0.3) under similar conditions except for the ultrasonication duration (2 min) and amplitude (40%), and crude load (0.05%, w/w). The findings show that the integrated system has a great potential to be employed as an alternative bioseparation scheme for SOD from microalgae.